The political economy of the fisheries sector in Uganda: ruling elites, implementation costs and industry interests - Mette Kjær, Anne; Muhumuza, Fred; Mwebaze, Tom; Katusiimeh, Mesharch (DIIS, 2012)
This paper sets out to explain policies, implementation arrangements and results (PIRs) in Uganda’s fisheries sector. Industry actors wanted to be able to keep up with European standards in order to survive in the chilled and frozen fillet export industry. They put pressure on ruling elites to support the establishment of effective hygiene and testing procedures. This helped the fishing industry succeed to an extent that helped create interests in the status quo. Fishermen, their dependents, and the fish processors all wanted to maintain a high level of fish catches. It was politically costly for ruling elites to enforce fisheries management because strict enforcement was unpopular with fishermen, as well as with many fishermen and security agents who benefitted from illegal fishing. Therefore, the success was not maintained: a pocket of efficiency was established with regard to hygiene and testing, but not with regard to enforcing fisheries management. Overfishing and the near collapse of the fishing sector were the results.